PERANAN GOOD CORPORATE GOVERNANCE PADA PERUSAHAAN TRAKINDO UTAMA - Sonbait, Gad Edison (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2023)
Companies and organizations must implement good governance because they can regulate and manage companies so as to generate added value for the company and shareholders. This study aims to analyze the role of good corporate governance in the company Trakindo Utama by using literature. The results of the study show that Trakindo Utama has implemented the five main principles of GCG, namely accountability, fairness, transparency, independence and responsibility. Good corporate governance is important for various companies to implement in order to build partnership relationships and shareholder trust and encourage growth in the company's profitability in the long term.